2018
DOI: 10.1136/bmjoq-2017-000070
|View full text |Cite
|
Sign up to set email alerts
|

Improving local anaesthetic systemic toxicity (LAST) awareness in maternity care using tailored educational tools

Abstract: Local anaesthetic (LA) agents are widely used in maternity care. Although relatively safe, their use does carry risks, the most serious of which is systemic toxicity (LAST). LAST poses a major threat to maternal and neonatal safety due to the frequency of LA administration in maternity care and the under-recognition of toxicity in such settings, which has been reported globally. Our aim was to prevent LAST occurrence in a District General Hospital (DGH) maternity unit by improving staff awareness through the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…However, teaching programs led to a significant improvement in knowledge. 18 A Danish study conducted among anesthetists, revealed that about 50% knew about lipid therapy but were not aware how to acquire ILE. 19 In a cross-sectional study in Turkey, 42% of the emergency physicians identified ILE dosage.…”
Section: Discussionmentioning
confidence: 99%
“…However, teaching programs led to a significant improvement in knowledge. 18 A Danish study conducted among anesthetists, revealed that about 50% knew about lipid therapy but were not aware how to acquire ILE. 19 In a cross-sectional study in Turkey, 42% of the emergency physicians identified ILE dosage.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Edwards et al at demonstrated an overall deficit in knowledge on LAST (including ILE therapy) in a Maternity unit in a UK Hospital. However, teaching programmes led to a significant improvement in knowledge [23] . A Danish study in 2011, conducted among anaesthetists, revealed that around 50% knew about lipid therapy but were not aware how to acquire ILE and that it was not available at places where LA was administered [24] .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Edwards et al which aimed to improve LAST awareness showed that the average baseline (preassessment) scores were 3.87/14 with a standard deviation of 3.18. Average postvideo presentation scores were 6.57 with a standard deviation of 3.52 [ 9 ]. Thus, the difference in mean response was 2.7.…”
Section: Methodsmentioning
confidence: 99%
“…As such, any practitioner, not limited to the anaesthesiologist, who administers these agents should be familiar with the prevention, identifcation, and treatment of LAST. Despite the limited data, several studies have shown that knowledge of LA doses and awareness of LAST remains poor among clinicians [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation